Improving Access to Justice in Kenya through Horizontal Application of the Bill of Rights and Judicial Review (Strathmore Law Review, 2017)
Article 20 of the Constitution of Kenya 2010 states that the Bill of Rights binds all state organs and all persons. However, the extent to which natural persons and private legal persons can be held liable for human rights violations has become an issue. The courts have differed and provided mixed directions as to liability for human rights violations by private persons. Under the previous constitutional era, only decisions of public entities could be reviewed through judicial review. This article is an attempt to illustrate, with the aid of case law, the increased possibility for access to justice by the litigant in constitutional rights matters post-2010. We move from the previous era where human rights could not generally be sought against private persons to one where there is an attitude of acceptance, albeit a very cautious one, where rights can now be sought against any private persons. Also, there is hope for justice and a better society in general, if private bodies’ decisions can also be judicially reviewed. Private entities wield immense power over individuals and it is crucial to lift the veil of privacy and go to the root of the matter by evaluating their decision-making processes.